2022
DOI: 10.1186/s12910-022-00856-y
|View full text |Cite
|
Sign up to set email alerts
|

What information and the extent of information to be provided in an informed assent/consent form of pediatric drug trials

Abstract: Background This study aimed to determine the elements and the extent of information that child participants and their parents would like to read in an informed assent form (IAF)/informed consent form (ICF) of a pediatric drug trial. Methods A descriptive survey was conducted to determine the perceived importance of each element of the ICF content from child participants and their parents who underwent informed assent/consent of a multi-center pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
5
0
4
Order By: Relevance
“…Se seleccionaron científicos, doce eran estudios cuantitativos [22][23][24][25][26][27][28][29][30][31][32][33] ocho cualitativos [34][35][36][37][38][39][40][41] . Los lugares de origen de los estudios fueron Estados Unidos 26,27,[29][30][31]39 , Brasil 28,34,40 , Tailandia 24 , Jordania 37,38 , Malawi 41 , Europa 22,23,25,32,33,35,36,39 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Se seleccionaron científicos, doce eran estudios cuantitativos [22][23][24][25][26][27][28][29][30][31][32][33] ocho cualitativos [34][35][36][37][38][39][40][41] . Los lugares de origen de los estudios fueron Estados Unidos 26,27,[29][30][31]39 , Brasil 28,34,40 , Tailandia 24 , Jordania 37,38 , Malawi 41 , Europa 22,23,25,32,33,35,36,39 .…”
Section: Resultsunclassified
“…La literatura encontrada no permite determinar claramente a partir de qué edad un niño puede tomar decisiones válidas y consentir sobre su participación en una investigación 34,41 . Sin embargo, los factores que más influye en la competencia de los NNA para consentir sería su desarrollo cognitivo 23,31,34 , madurez 41 , sistemas sociales 34 , normativas legales, aspectos culturales, religiosos y educativos 22,24,37,38 .…”
Section: Edadunclassified
“…Deciding on the depth and width of information required to make an informed and voluntary decision, without overwhelming children and parents, can be a difficult task. Health benefits and side-effects related to trial participation have been reported to be the most valued and relevant information for families considering participation in drug trials (Koonrungsesomboon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For patients, age-appropriate models may be needed to help minors and their substitute decision-makers understand the concept of assent and their roles in the process (Weisleder, 2020 ). Maximizing the relevant, lay information necessary to understand the risk–benefit profiles of planned medical procedures coupled with novel communication mediums (Koonrungsesomboon et al, 2022 ), such as using age-appropriate multimedia assent documents (Wongthai et al, 2022 ), are one step toward addressing this need for patient education. Third, there can exist exceptional scenarios where seeking assent from children with developing capacity may be overridden if there exists a significant benefit to the child and their wellbeing would be jeopardized otherwise (Moran et al, 2011 ).…”
Section: Informed Consent Frameworkmentioning
confidence: 99%